The safety of the posterior ankle arthroscopy in management of posterior ankle impingement: A cadaveric study. (June 2016) - Lui, T.H.; Chan, L.K.
Highlights: Posterior ankle arthroscopy can manage posterior ankle impingement in supine position. Associated intra-articular pathology and anterior ankle impingement can be dealt with without the need of change of patient positioning. Posteromedial portal is just anterior to the posterior tibial tendon and posterolateral portal is just posterior to the peroneal tendons. The coaxial portals are not suitable for treating the Achilles tendon pathology especially the insertional problem. Abstract: Background: Arthroscopic management of the posterior ankle impingement with the patient in supine position has the advantage of dealing with anterior ankle pathology at the same time without the need to change position of the patient. This study aims at evaluation of the safety of portal establishment and instrumentation of this technique. Methods: Sixteen fresh-frozen cadaver specimens were used. The relationships of the posteromedial and posterolateral portals to the adjacent tendons and nerves and the relationship of the coaxial portal tract with the posterior ankle capsule and the flexor hallucis longus tendon were studied. Result: Angle θ 1 between the intermalleolar line and the posterior ankle coaxial portal tract averaged 1° (−10° to 22°). Angle θ 2 between the intermalleolar line and the metal rod where the neurovascular bundle started to move averaged 19° (10° to 30°). Angle θ 3 between the intermalleolar line and the metal rod where it reached the lateral border of the Achilles tendon was larger than angle θ 2 in all specimens. The angle of safety ( θ s ) averaged 18° (−1° to 26°). Conclusions: Injury to the tendon, nerves or vessels is possible during establishment of the portals and resection of the os trigonum.